2014
DOI: 10.1016/j.urology.2014.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Concordance and Clinical Significance of Uncommon Variants of Bladder Urothelial Carcinoma in Transurethral Resection and Radical Cystectomy Specimens

Abstract: Abstract\ud OBJECTIVE:\ud To evaluate the concordance and prognostic role of histologic variants of bladder urothelial carcinoma in transurethral resection of bladder tumor (TURBT) and radical cystectomy (RC) specimens.\ud METHODS:\ud Clinicopathologic information available at the time of RC and follow-up data from 4110 RC specimens, collected between January 2000 and December 2009 at 17 tertiary referral centers were retrospectively analyzed and evaluated for the presence or absence of uncommon variants of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…In particular the concordance depended on the type of variant histology and was low in general and micropapillary variant, and high for sarcomatoid, small cell, and squamous variants. Similar result was shown in a multicenter study by Cai et al (22) who reported a lack of agreement for uncommon variants between TUR and RC in the entire population (P<0.001). However, Abufaraj et al (23), reported a high concordance rate between the two specimens (about 84%), with a TUR’s specificity of 99% and negative predictive value (NPV) of 83%.…”
Section: Accuracy Of Turbtsupporting
confidence: 89%
“…In particular the concordance depended on the type of variant histology and was low in general and micropapillary variant, and high for sarcomatoid, small cell, and squamous variants. Similar result was shown in a multicenter study by Cai et al (22) who reported a lack of agreement for uncommon variants between TUR and RC in the entire population (P<0.001). However, Abufaraj et al (23), reported a high concordance rate between the two specimens (about 84%), with a TUR’s specificity of 99% and negative predictive value (NPV) of 83%.…”
Section: Accuracy Of Turbtsupporting
confidence: 89%
“…In one multicenter study, more than half men with variant histology noted upon radical cystectomy specimen analysis were not diagnosed with variant histology at TURBT. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 10-25% of bladder cancers have a component of variant histology [47][48][49][50]. The World Health Organization and International Consultation on Bladder Cancer recognizes more than 10 unique histologic variants in bladder cancer [46,51], summarized in Table 3.…”
Section: Pathologymentioning
confidence: 99%
“…Pure variant histology in particular may confer a distinct clinical behavior and tends to have a high propensity for relapse [52][53][54]. Variant histology is often challenging to identify on TURBT specimens [48,55]. As a result, pathology review by an experienced GU pathologist can be informative, and lead to major changes in management [43,44].…”
Section: Pathologymentioning
confidence: 99%